Neonatal leukaemia - Roberts, I; Fordham, N; Rao, A; Bain, B (Wiley, 2018)
Neonatal leukaemia is defined as occurring within the first 28 days of life and most, if not all, cases are congenital. With the exception of Down syndrome‐associated transient abnormal myelopoiesis, which is not considered here, neonatal leukaemias are rare. In two‐thirds of patients the disease manifests as an acute myeloid leukaemia, frequently with monocytic/monoblastic characteristics. Most other cases are acute lymphoblastic leukaemia, particularly B lineage, but some are mixed phenotype or blastic plasmacytoid dendritic cell neoplasms. The most frequently observed cytogenetic/molecular abnormality is t(4;11)(q21.3;q23.3)/KMT2A‐AFF1 followed by t(1;22)(p13.3;q13.1)/RBM15‐MKL1 and t(8;16)(p11.2;p13.3)/KAT6A‐CREBBP. Common clinical features include prominent hepatosplenomegaly and a high incidence of skin involvement, sometimes in the absence of bone marrow disease. A distinctive feature is the occurrence of spontaneous remission in some cases, particularly in association with t(8;16). In this review, we summarise current knowledge of the clinical, cytogenetic and molecular features of neonatal leukaemia and discuss clinical management of these cases.